Gender differences and trends in the participation of Malaysians in education: implications on employment outcomes - Ahmad, Aminah (The Journal of International Management Studies, 2009)
This study examined gender differences and trends in the participation of Malaysians in education. Trend data for the period between 1990 and 2007 were calculated and compiled from annual reports of the Ministry of Education, and the Department of Statistics, Malaysia. Percentages of male and female student enrollment in government primary, secondary, pre-university, and college and university education, and the percentage distribution of male and female teaching staff in schools, teachers’ training institutes and polytechnics were presented. The findings revealed that there existed gender differences in the student enrollment in favour of males in vocational and technical schools, as well as in polytechnics. However, in pre-university institutions, teachers training colleges and institutes, and in universities the proportion of female students exceeded males. Overall the trend in the participation of women in education was very encouraging since the percentages of females in the different levels of education were on the increase. In terms of specialization, although there were still fewer females in traditionally male-dominated fields such as engineering, architecture, town planning, quantity surveying, technical and vocational skills, the proportions of females in these specializations were on the increase. However, the females exceeded the males in the field of science, which encompasses basic sciences, environmental science, agriculture, home science, food technology, computer science and medicine. The participation of females in the science field steadily increased over the years. There were also more females in the arts field which include specializations such as commerce, economics, business, accounting, management, administration, communication, law, social science, humanities and languages, as well as in the field of education, and the proportions in such specializations were on the increase. Implications of the findings on employment outcomes were discussed.